1998
DOI: 10.1017/s1355838298980542
|View full text |Cite
|
Sign up to set email alerts
|

Recombination, RNA evolution, and bifunctional RNA molecules isolated through Chimeric SELEX

Abstract: Exchange of RNA structural domains through recombination can be used to engineer RNAs with novel functions and may have played an important role in the early evolution of life. The degree of function an RNA element retains upon recombination into a new sequence context is a measure of how deleterious or beneficial recombination will be. When we fused pairs of aptamers previously selected to bind coenzyme A, chloramphenicol, or adenosine, the chimerae retained some ability to bind both targets, but with reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Although the ribozyme variants isolated from this pool were not faster than the ribozyme used to build it, some were considerably smaller. It is also known that recombination between different aptamer domains can generate molecules with the binding properties of both parental aptamers (Burke and Willis 1998), and recombination by randompriming was used in combination with several other approaches to improve the activity of an RNA polymerase ribozyme (Wochner et al 2011). In this study, we found that recombination of point mutations by synthetic shuffling was an effective way to further improve a kinase ribozyme that had been previously improved by random mutagenesis and reselection: the activity of the most efficient kinase ribozyme isolated was 30-fold greater than that of the most efficient kinase used to build the synthetically shuffled pool and 1300-fold faster than that of the initial isolate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ribozyme variants isolated from this pool were not faster than the ribozyme used to build it, some were considerably smaller. It is also known that recombination between different aptamer domains can generate molecules with the binding properties of both parental aptamers (Burke and Willis 1998), and recombination by randompriming was used in combination with several other approaches to improve the activity of an RNA polymerase ribozyme (Wochner et al 2011). In this study, we found that recombination of point mutations by synthetic shuffling was an effective way to further improve a kinase ribozyme that had been previously improved by random mutagenesis and reselection: the activity of the most efficient kinase ribozyme isolated was 30-fold greater than that of the most efficient kinase used to build the synthetically shuffled pool and 1300-fold faster than that of the initial isolate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vitro selection experiments have shown that the ligation and exchange of RNA structural domains through recombination can be used to engineer new functional RNAs (Burke and Willis 1998;Joyce 2004). It is of particular interest how the evolution of the class I ligase ribozyme (Bartel and Szostak 1993), appended with a track of 76 random nucleotides at its 39 end, allowed the selection of a 189-nt-long template-dependent RNA polymerase ribozyme (Johnston et al 2001).…”
Section: A Stepwise Model For the Origin Of The Rna Worldmentioning
confidence: 99%
“…However, if the problematic sequence components cannot be readily identified the required optimization of fused properties can be addressed directly by SELEX itself. This concept was demonstrated early by Burke and Willis who optimized fused aptamers against very divergent cytoplasmic small molecule targets [14]. Another critical question is how much cargo needs to be delivered for efficacy if the delivered nucleic acid encoded functionality is catalytic of otherwise amplified in nature.…”
Section: General Properties Of Aptamers As a Reagent Class—why Chomentioning
confidence: 99%